2016
DOI: 10.1007/s11096-016-0394-2
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacists’ awareness, knowledge and attitude about childhood autism in Istanbul

Abstract: Background Being one of the key players in healthcare, pharmacists could have an important role in the early detection and care of children with autism, by familiarizing themselves with autism-related resources and helping families to find relevant professional resources. Objective The purpose of this study was to determine the awareness of pharmacists about autism, and their knowledge and attitude towards autism. Setting İstanbul Province of Turkey. Method This descriptive study was carried out in pharmacists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
13
0
4
Order By: Relevance
“…Concerning the role of pharmacists, as a health professionals, they should be informed about the general characteristics and current treatments of ASD, in order to provide early awareness to the families of children who may be autistic, and to direct them to the physician in the proper time. They should contribute to the positive outcomes of the treatment by ensuring the correct use of the drugs prescribed to the children and adolescents diagnosed with autism (Wongpakaran et al 2017;Luleci et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the role of pharmacists, as a health professionals, they should be informed about the general characteristics and current treatments of ASD, in order to provide early awareness to the families of children who may be autistic, and to direct them to the physician in the proper time. They should contribute to the positive outcomes of the treatment by ensuring the correct use of the drugs prescribed to the children and adolescents diagnosed with autism (Wongpakaran et al 2017;Luleci et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists play an important role in the follow up of new treatment approaches, in providing the correct use of the prescribed drugs and over the counter medications (OTC), as well as the education of ASD families. Unfortunately, pharmacists are rarely included in the team of health professionals who routinely provide care to children with ASD (Shafiq and Pringsheim 2018;Breik et al 2018;Wongpakaran et al 2017;Luleci et al 2016).…”
mentioning
confidence: 99%
“…In the literature, awareness of ASD has been evaluated in many groups such as pediatricians, psychiatrists, neurologists, family physicians, pharmacists, educators, psychologists, and speech therapists throughout the society (3,16,17,22,24). One of the early medical contacts of children who have not yet been diagnosed with ASD may be with ENT physicians whom they are brought with suspicion of hearing and communication problems.…”
Section: Discussionmentioning
confidence: 99%
“…"Autism Spectrum Disorder Awareness Questionnaire" is a questionnaire containing the findings that can be evaluated during a routine ENT examination of a possible ASD child and suggesting possible ASD, and consists of two parts as "basic questions" and "optional questions". This questionnaire was prepared in the light of the current literature (11,(16)(17)(18)(19)(20)(21)(22)(23) to observe a possible ASD in a child who applied to an ENT physician for any reason. The basic part questions the findings that are important to be known by physicians, and are more common and easier to recognize and consists of 19 questions.…”
Section: Methodsmentioning
confidence: 99%
“…There have been no reported studies in Australia to assess the understanding of ASD by community pharmacists or the appropriateness of community pharmacies for individuals with ASD. Studies conducted in the USA, Turkey and Palestine have reported gaps in pharmacists’ understanding and knowledge of ASD . Two other studies have been reported involving other health professionals that assessed knowledge and understanding of ASD .…”
Section: Introductionmentioning
confidence: 99%